Assessing practices of organic vegetable production in Bhadaure Tamagai, Kaski, Nepal - Bhurtyal, Saraswati; Dangol, Dharma Raj; Joshi, Ananda Raj (Journal of Agriculture and Environment, 2015)
This study assessed local practices of organic vegetable production through two focus group discussions and a household survey with 66 randomly selected households of ward number 1 and 2 of Bhadaure Tamagi Village Development Committee, Kaski district of Nepal. The study found that most of the farmers were growing varieties of organic vegetables by using local practices for household consumption as well as for marketing mainly by using livestock manure, and organic biopesticides prepared locally. In addition, organic vegetable production in the area has helped to increase their income and contributed to strengthen traditional seed exchange practice, conservation of local seeds and agro biodiversity. In order to sustain current production trend and enhance marketing of organic vegetables, the study recommends targeted interventions of organic farming related to capacity building, technology support and market promotion of the produces.